Optimasi Proses Produksi Menggunakan Metode Lean Manufacturing pada Industri Otomotif - Ahmad Rizky Pratama (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The automotive industry is a highly competitive sector requiring continuous improvement in efficiency and productivity. Lean Manufacturing has emerged as a powerful methodology for eliminating waste and optimizing production processes. This study aims to implement and evaluate the effectiveness of Lean Manufacturing tools in improving the production process of a selected automotive company in Indonesia. A qualitative and quantitative approach was employed, including value stream mapping, waste identification, and implementation of tools such as 5S, Kaizen, and Kanban. Data were collected through direct observation, interviews, and production records. The findings indicate a significant reduction in lead time by 23%, a 17% increase in production output, and enhanced workflow efficiency. The study concludes that Lean Manufacturing significantly contributes to process optimization in the automotive industry and offers practical implications for managers seeking operational excellence.